DEPOSITIONAL ENVIRONMENT STUDY OF KASAI FORMATION LEBAN AREA AND SURROUNDINGS, RANTAU PANDAN DISTRICT, BUNGO DISTRICT, JAMBI - Bagus, Bagus Adhitya; Khairina, Atika; Ahmad Mahbub, Itang (KURVATEK, 2023)
The Leban area is one of the areas in Jambi which is very interesting for conducting geological studies related to sedimentology, tectonics and paleontology. One of the interesting objects to be reviewed is the Kasai Formation, where a description of this formation still requires further research. Here the study of the Kasai formation is viewed from its sedimentology, especially regarding the Depositional Environment. The Kasai Formation in the Leban and Surrounding Research Area, Bungo Regency, Jambi Province. From the stratigraphic cross-sectional measurements, 6 facies were found in each rock unit, namely the Planar cross-turf tuff (Sp) facies, the tuff sandstone (Sm) facies, the ripples cross lamination (Sr) sandstone facies, the very fine sandstone facies ( Sm) and the Tuff Claystone Facies (Fm).